2015
DOI: 10.1186/s13617-015-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of probabilistic volcanic hazard map properties on hazard communication

Abstract: Probabilistic volcanic hazard analysis is becoming an increasingly popular component of volcanic risk reduction strategies worldwide. While probabilistic hazard analyses offer many advantages for decision-making, displaying the statistical results of these analyses on a map presents new hazard communication challenges. Probabilistic information is complex, difficult to interpret, and associated with uncertainties. Conveying such complicated data on a static map image without careful consideration of user persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 48 publications
0
100
1
Order By: Relevance
“…Haynes et al (2007) evaluated the effectiveness of volcanic hazard maps as communication tools on Montserrat, West Indies and found that the use of aerial photographs as a basemap improved people's ability to comprehend hazard information compared to traditional contour basemaps. In general, it has been found the public do not comprehend maps well and professional design input guided by iterative evaluation of map comprehension is wise (Haynes et al 2007;Thompson et al 2015). In contrast to the public, more specialist stakeholders such as infrastructure managers may require more detailed and hazard specific information about the impacts, location and recommended actions to inform decisions on land-use and building strength e.g.…”
Section: Communication and Risk Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haynes et al (2007) evaluated the effectiveness of volcanic hazard maps as communication tools on Montserrat, West Indies and found that the use of aerial photographs as a basemap improved people's ability to comprehend hazard information compared to traditional contour basemaps. In general, it has been found the public do not comprehend maps well and professional design input guided by iterative evaluation of map comprehension is wise (Haynes et al 2007;Thompson et al 2015). In contrast to the public, more specialist stakeholders such as infrastructure managers may require more detailed and hazard specific information about the impacts, location and recommended actions to inform decisions on land-use and building strength e.g.…”
Section: Communication and Risk Management Strategiesmentioning
confidence: 99%
“…for colour blind readers), content, and key expression (Haynes et al 2007;Thompson et al 2015). Haynes et al (2007) evaluated the effectiveness of volcanic hazard maps as communication tools on Montserrat, West Indies and found that the use of aerial photographs as a basemap improved people's ability to comprehend hazard information compared to traditional contour basemaps.…”
Section: Communication and Risk Management Strategiesmentioning
confidence: 99%
“…As we have outlined in this chapter however, there are issues with using a one-size-fits-all communication product. This was also identified by Thompson et al (2015) in using probabilistic volcanic hazard maps. We found that taking into account the local context is vital, which supports the findings of numerous recent research in volcanic crisis communication (Haynes et al 2007;Fearnley et al 2012;Potter et al 2014).…”
Section: Volcanic Crisis Communicationmentioning
confidence: 99%
“…Thompson et al (2015) have noted that map properties (such as colour schemes and data classification schemes chosen) can influence how users engage with and interpret probabilistic volcanic hazard maps.…”
Section: Ash Forecasting Productsmentioning
confidence: 99%